(Be)Ständige digitale Metamorphosen?! – »perhaps there will always be something more« - Carina Hoff (Zeitschrift für digitale Geisteswissenschaften)
The act of digital editing is permanently in flux, and it is currently located between medial experimentation, the text-critical attachment to tradition, and standardization. This experimental character can be subsumed under keywords such as multiperspectivity, multidisciplinarity, and trans- or multimediality. These keywords serve as the (re)productive power driving the permanent pursuit of more, which was initiated by the shift in format, with its changing research interests and goals. However, the corresponding medial and material metamorphoses produce the dilemma of a documentary level of detail in the digital edition that requires new strategies for use. As these new possibilities take digital editing to its limits, the next question is where its future direction will lead.